Inovasi Olahan Lele oleh Kelompok Bunda Koja sebagai Strategi Pemberdayaan Masyarakat Area PT. Pertamina (Persero) Integrated Terminal Jakarta - Andri Akbar; Ryan Hendra; Anita Ervina; Rida Aini Rahmawati (Institut Pertanian Bogor, 2021)
Knowledge about food nutrition for toddlers and the ability to buy nutritious food are important factors in toddlers parenting. Kelurahan Rawa Badak Selatan (KRBS) is one of area in Koja Subdistrict, North Jakarta which dominated by toddlers whose nutritional status needs to be improved. CSR PT. Pertamina Integrated Terminal Jakarta carried out the Serba Unsur Lele (SULE) program as a community empowerment strategy by create various product innovations from catfish and catfish bone by-product. The aim of this activities is Bunda Koja community, including mothers of toddlers, are able to improve the knowledge and skills of catfish products processing and build a growing business, some products that routinely given to toddlers are expected to give a positive impact for toddler nutrition. This program consisted of training and the application of mentoring. The series of programs include training on catfish products innovation training, management of catfish production, and product marketing. The innovations been developed for production is nuggets, abon, and catfish stick. Catfish bones by- product are processed into crackers, tempe chips, and fish bone biscuits. Abon, nuggets, crackers and tempeh chips have been through the production and marketing stages. This activity succeeded in having a positive impact especially for mothers of toddlers, could receive the additional income from the catfish product business. The more catfish products innovation which will be developed is expected to become a business so that it can have a positive impact on the economy of the Bunda Koja community, mothers of toddlers, and the surrounding community.